1993
DOI: 10.1016/s0022-5347(17)36253-5
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Bladder Perfusion in Interstitial Cystitis: A Study of Blood Supply Using Laser Doppler Flowmetry

Abstract: Laser doppler flowmetry was used to study bladder blood flow in 16 patients with interstitial cystitis and in 18 control subjects. All studies were performed at cystoscopy under general anesthesia. Interstitial cystitis patients conformed to the diagnostic criteria of the National Institute of Diabetes and Digestive and Kidney Diseases (NIDDK). Blood flow measurements were made at four specific sites in the bladder at a capacity of 100 ml. and at full capacity. The mean maximum capacity under anesthesia was 82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 9 publications
1
52
0
2
Order By: Relevance
“…However, Irwin and Galloway [15] using laser flowmeter reported an increase in the blood flow rate after distension of the human bladder. Contradictory findings regarding the change in blood flow in the bladder with bladder distension are probably due to the difference in method, species, and in the degree of distension of the bladder.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, Irwin and Galloway [15] using laser flowmeter reported an increase in the blood flow rate after distension of the human bladder. Contradictory findings regarding the change in blood flow in the bladder with bladder distension are probably due to the difference in method, species, and in the degree of distension of the bladder.…”
Section: Discussionmentioning
confidence: 98%
“…Subsequently the mean value of the three observations was taken as the blood flow to the each bladder. Since both the structure of the microcirculation and the spectrum of the reflected laser affected by physical characteristics differ in each tissue, it is not accurate to obtain the absolute value of the blood flow rate (ml/min/100 g) as reported by other authors [14,15] even with any kind of amplification or calibration. However, when blood flow is measured in the same tissue, changes (in arbitrary numbers) on the flowmeter are proportional to the changes in blood flow.…”
Section: Measurement Of Regional Blood Flow To the Urinary Bladdermentioning
confidence: 98%
“…Irwin and Galloway reported that the bladder is relatively ischemic during bladder filling in patients with IC compared to those without IC. 1 Pontari et al showed that bladder perfusion decreased and increased with bladder filling in patients with and without IC, respectively. 2 Tamaki et al showed that neovascularization in IC bladder promoted by angiogenic growth factors has an important role in the pathogenesis of IC, inducing glomerulations during hydrodistension.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed pathological findings of IC/PBS focusing on ischemia and a reduction in bladder capacity due to fibrosis of the bladder wall. [1][2][3] Indeed, hyperbaric oxygen therapy has been reported to be effective in patients with IC/PBS resistant to conventional treatments. 4,5 Oxidative stress due to free radicals, which are formed by reperfusion after bladder ischemia, can cause bladder damage.…”
Section: Introductionmentioning
confidence: 99%
“…The integrity and function of the urothelium is extremely sensitive to ischaemia, acute overdistension, diabetes, partial outlet obstruction, and hypoxia Levin et al 1990b;Monson et al 1991Monson et al , 1992Monson et al , 1994Tong et al 1992;Eika et al 1993;Tammela et al 1993). A reduction in blood flow has been linked to a variety of disorders including interstitial cystitis, recurrent urinary tract infections and incontinence Irwin & Galloway, 1993). In addition, current studies indicate that both bladder distention and hypertrophy secondary to partial outlet obstruction result in a cyclical reduction of blood flow and ischaemia Siroky et al 1993;Lin et al 1995;Greenland & Brading, 1996;Brading, 1997;Greenland et al 1997).…”
Section: E T a B O L I S M A N D E N E R G E T I C Smentioning
confidence: 99%